Bimaterial interface crack analysis using an extended consecutive-interpolation quadrilateral element - Truong, Thien Tich; Tran, Bang Kim; Lo, Vay Siu; Nguyen, Nha Thanh; Nguyen, Minh Ngoc (Vietnam Journal of Science and Technology, 2022)
A very important problem in the research of layer structures is the modeling of cracks on the material interface. Due to the complex physical and mechanical properties of this structure, the simulation of discontinuities such as cracks and material interface by traditional finite element methods requires a very fine mesh density. Furthermore, mesh smoothing requires a really large amount of computational resources. Therefore, the extended algorithm which does not require the remeshing technique was born to solve the crack problems. In this paper, the extended consecutive-interpolation finite element method (XCFEM) is employed to modeling the mix-mode interface cracks between two dissimilar isotropic materials. The XCFEM using 4-node consecutive-interpolation quadrilateral element (XCQ4) provides continuity of nodal gradient due to the concept of “consecutive-interpolation” so that the stress and strain fields derived from XCQ4 is smoother than that obtained by the classical FEM element. The accuracy and effectiveness of the method are demonstrated via various numerical examples and compared with other researches.